Plantar Purpura as the Initial Presentation of Viridians Streptococcal Shock Syndrome Secondary to Streptococcus gordonii Bacteremia - Chen-Yi Liao; Kuan-Jen Su; Cheng-Hui Lin; Shu-Fang Huang; Hsien-Kuo Chin; Chin-Wen Chang; Wu-Hsien Kuo; Ren-Jy Ben; Yen-Cheng Yeh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Viridians streptococcal shock syndrome is a subtype of toxic shock syndrome. Frequently, the diagnosis is missed initially because the clinical features are nonspecific. However, it is a rapidly progressive disease, manifested by hypotension, rash, palmar desquamation, and acute respiratory distress syndrome within a short period. The disease course is generally fulminant and rarely presents initially as a purpura over the plantar region. We present a case of a 54-year-old female hospital worker diagnosed with viridians streptococcal shock syndrome caused by Streptococcus gordonii. Despite aggressive antibiotic treatment, fluid hydration, and use of inotropes and extracorporeal membrane oxygenation, the patient succumbed to the disease. Early diagnosis of the potentially fatal disease followed by a prompt antibiotic regimen and appropriate use of steroids are cornerstones in the management of this disease to reduce the risk of high morbidity and mortality.